2010
DOI: 10.2144/000113419
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Imaging of Dual Gene Expression at the Single-Cell Level

Abstract: Bioluminescence imaging reveals the long-term dynamics of individual gene expression in a single cell. However, methods for simultaneously imaging multiple gene expression patterns have been unknown to date. Here, we constructed a dual-path optical luminescence imaging system using a two-color reporter system and could simultaneously track two gene expression patterns for several days in a single cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
(5 reference statements)
0
19
0
Order By: Relevance
“…However, a molecular imaging system based on a CCCD camera and the bright bioluminescence reporters enables real-time monitoring of the level, the localization, and the duration of the gene expression without cell lysis, which is required for investigating dynamic processes of cell differentiation and tissue regeneration [22]. Furthermore, advanced luciferase technology, involving progress in both the multicolor reporter system and the detection equipment, has allowed us to simultaneously monitor the expressions of multiple genes because luciferases can emit different colored light in the catalysis of a single D-luciferin substrate and each of the intensities can be quantified by splitting these mixed emission spectra with optical filters (Figure 1) [23,24,25]. …”
Section: Real-time Monitoring Of Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a molecular imaging system based on a CCCD camera and the bright bioluminescence reporters enables real-time monitoring of the level, the localization, and the duration of the gene expression without cell lysis, which is required for investigating dynamic processes of cell differentiation and tissue regeneration [22]. Furthermore, advanced luciferase technology, involving progress in both the multicolor reporter system and the detection equipment, has allowed us to simultaneously monitor the expressions of multiple genes because luciferases can emit different colored light in the catalysis of a single D-luciferin substrate and each of the intensities can be quantified by splitting these mixed emission spectra with optical filters (Figure 1) [23,24,25]. …”
Section: Real-time Monitoring Of Gene Expressionmentioning
confidence: 99%
“…In mammalian research, firefly luciferase has been used typically under the control of promoter elements from the Period1 (Per1), Period2 (Per2) or brain and muscle arnt-like 1 (Bmal1) genes [24]. Dual-color bioluminescence reporter systems using beetle luciferases enabled us to monitor simultaneously Bmal1 and Per2, which are responsible for circadian rhythm [25]. Bioluminescence imaging reported the peripheral tissues exhibit robust circadian rhythms in culture by monitoring gene expression of clock genes [26].…”
Section: Real-time Monitoring Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of molecular imaging in pre-clinical research is evolving. In small animal models optical imaging technologies are used to visualize normal as well as aberrant cellular processes at a molecular-genetic or cellular level of function (Chaudhari et al, 2005;Kwon et al, 2010;Snoeks et al, 2011).…”
Section: Pre-clinical Cancer Research Optical Imaging Modalitiesmentioning
confidence: 99%
“…These results indicated that we can evaluate the transformation efficiency of the reporter gene or the stability of the bioluminescent stable transformant cell. Although several examples for single-cell BLI as a relative light unit were reported [6,11,12], to our knowledge this is the first example of the absolute photon number being determined directly in a single-cell expressing luciferase. However, at present, absolute BLI could be limited to a mono-layer single-cell level.…”
mentioning
confidence: 99%